MODEL WACANA BERWAWASAN NILAI-NILAI KONSERVASI BERBASIS EKOLINGUISTIK SEBAGAI PENGAYAAN MATERI AJAR MATA KULIAH PENDIDIKAN LINGKUNGAN HIDUP - Yuniawan, Tommi (Universitas Negeri Semarang, 2016)
The purpose of this research mendeskripsi the model needs insightful discourse based conservation values ekolinguistik and designing the prototype insightful discourse based conservation values ekolinguistik .The methodology used in this research is research and development .The results of research while presented by , concluded the following .The level of the needs of the model discourse leads on aspects of student motivation , the aspect of matter or the contents of books , presentation of aspects , the aspect of the materials and keterbacaan , and the aspect of grafika .The prototype design insightful discourse based conservation values ekolinguistik referring to the seven pillars of the conservation i.e. the pillars of biodiversity , the pillars of clean energy, a pillar of green building and internal transport , nirkertas policy pillar , the pillars of waste management, the pillars of ethics art and culture , the pillars of conservation volunteers.